ENVIRONMENTAL LITERACY OF BIOLOGY EDUCATION STUDENTS - Nurlia, Nurlia; Ristiana, Evi; Aulia, Kurnia (JURNAL PENDIDIKAN GLASSER, 2024)
Environmental literacy needs to be possessed by the current generation for the sustanability of future generations come, as do teaching students who will play a role in educating furure generations. This research aims to determine the environmental literacy abilities of students with a larger research sample, not only students who take Environmental Knowledge and Management courses, but also all Biology Education students at FKIP Universitas Muhammadiyah Luwuk. This research used a descriptive method with a research sample of 33 Biology Education students. The data collected in this research were questions and questionnaires containing four domains in environmental literacy consisting of 15 questions regarding the knowledge aspect, 15 statements regarding the cognitive skills aspect, 9 statements regarding the attitude aspect and 8 statements regarding the behavioral aspect. The questionnaire is filled out by students online via Google Forms. The data obtained was analyzed quantitatively descriptively. The research results show that the overall environmental literacy abilities of Biology Education students at FKIP Universitas Muhammadiyah Luwuk are in the "high" category with a score of 172.08.